UFGT: The Key Enzyme Associated with the Petals Variegation in Japanese Apricot - Wu, Xinxin; Gong, Qinghua; Ni, Xiaopeng; Zhou, Yong; Gao, Zhihong (Frontiers in Plant Science, 2017)
Japanese apricot (Prunus mume Sieb.et Zucc.) is an important ornamental plant in China. One of the traits of petals color variegation is attractive, but its formation mechanism is unclear. In our study, RNA-seq technology was employed to characterize the transcriptome response to the mutation of ‘Fuban Tiaozhi’ associated with petals variegation in Japanese apricot. As a result, 4,579,040 (white-flowered, WF) and 7,269,883 (red-flowered, RF) reads were mapped to P. persica genes, while 5,006,676 (WF) and 7,907,436 (RF) were mapped to P. persica genomes. There were 960 differentially expressed genes (DEGs) identified. Gene ontology analysis showed that these genes involved in 37 functional groups including 19 biological processes, 10 cellular components and eight molecular functions. Pathway enrichment annotation demonstrated that highly ranked genes were associated with flavonoid biosynthesis, anthocyanin biosynthesis, anthocyanins transports, plant hormone signal transduction and transcriptional factors. The expression patterns part of them were validated by qRT-PCR. We found that UDP-glucose: flavonoid 3-O-glucosyltransferase (UFGT) gene showed differential expression pattern. The UFGT enzyme activities in RF had a significantly higher than that of WF and lower in the initial stage and increased when the red appeared in the petals, which is identical to the accumulation of anthocyanins. And we also validated the SNPs, leading to the nonsynonymous mutations, in the UFGT by Sanger sequencing which may affect the enzyme activity. In summary, our results provide molecular candidates for better understanding the mechanisms of the variegation in Japanese Apricot.